EVALUASI SISTEM PENYEDIAAN AIR BERSIH MENGGUNAKAN SOFTWARE WATERCAD DI DESA BATUNGSEL KECAMATAN PUPUAN KABUPATEN TABANAN - Yekti, Mawiti Infantri; Harmayani, Kadek Diana; Krisnahadi, I Nyoman Dharma (JURNAL SPEKTRAN, 2020)
Batungsel Village utilizes clean water sourced from Sumber Tumpang Telu with existing water discharge from 2 (two) adjacent springs as much as 5,348 liters / second and 7,109 liters / second. At present, almost 20% of the community has not been served with clean water, and the existing distribution pipeline system has been able to meet 2 (two) existing banjars, namely the Batungsel Kelod and the Batungsel Kaja banjar. The results of the analysis of population growth projections show the arithmetic method which has the smallest standard deviation value. The average clean water needs for Batungsel village until 2033 are Banjar Batungsel Kelod at 1.75 liters / second, Banjar Batungsel Kaja at 2.71 liters / second, Banjar Dinas Pempatan at 0.01 liters / second and clean water needs at the development phase of the Dinas Pempatan banjar is 1.20 liters / second. The simulation results of the WaterCAD V8i program provide simulation results with pipes that do not meet the speed requirements, so that at the development stage a pipe diameter change is made according to the planning criteria and the development stage in the Pangkalan Service Office with the WaterCAD V8i program has met the planning standards. The development phase is planned to use PVC pipe class S-10 which is able to withstand a maximum pressure of 12.5 atm with fixed demand requirements or average water requirements of 0.11 liters / second.